Cocamidopropyl Betaine Catalyzed Benzoin Condensation and Pseudo-Four-Component Reaction of the in Situ Formed Benzoin in Water - Tamaddon, Fatemeh; Alizadeh, Masoomeh (Synlett, 2015)
An improved synthesis of benzoins, as key synthetic building blocks, and substituted pyrroles in micelle medium using a very small amount of cocamidopropyl betaine in water is described. In this one-pot strategy, benzoin condensation of aldehydes and further pseudo-four-component reaction of the in situ formed benzoin with 1,3-dicarbonyls, and ammonium acetate gave excellent yields of the desired pyrrole products.
Keywords: pseudo-four-component reaction; water; pyrrole; CAPB; zwitterionic surfactant; benzoin condensation; worm-like micelles